CLINICAL AND ANTI-INFLAMMATORY EFFECTS of THYMUS EXTRACT MOUTHWASH in PATIENTS WITH GINGIVITIS - RAMADHAN , LANA IBRAHIM; RASHID, SHERZAD KHORSHEED (Journal of Duhok University, 2023)
Herbal medicines have been using in dentistry clinics for a long history for preventing growth of microorganisms and their effects on inflammation. This novel study aimed to evaluate Thymus vulgaris (T. vulgaris) mouthwash in the treatment of gingivitis in comparison with chlorhexidine mouthwash. Patients attended periodontics department of College of Dentistry at the University of Duhok with age ranges of 15-35 years old from both sexes (females =23, males=22) were included in the study. Following the preparation of alcoholic Thymus extract 5% mouth wash, the mouthwash pH was measured on days 3, 6, 9, 12, 15, 21 and 60. The patients were randomly divided into three groups of deionized water, T. vulgaris (5.00%) and chlorhexidine and rinsed twice daily for 21 days. Plaque index (PI), gingival index (GI) were assessed on days 0, 14 and 21 and salivary levels of interleukin-6 (IL-6) were assessed at baseline and day 21. There were not significant changes in pH of T. vulgaris extract mouthwash on different days. However, the treatment with T. vulgaris mouthwash decreased PI, GI and the levels of salivary IL-6 as compared with baseline (P=0.001). The results showed non significant differences between T. vulgaris and chlorhexidine mouth washes for PI, GI and IL-6 in all the days (P>0.05). The efficiency of T. vulgaris mouthwash was increased with increasing time (21 days vs 14 days). In conclusion, T. vulgaris mouthwash can be used as an alternative for chlorhexidine for treatment of gingivitis